Application of behaviour change techniques to motor-skill development and health promotion in young adults: A narrative review - Huang, Ping; Saibon, Jamalsafri Bin; Hamzah, Aswati Binti; Xue, Yangguang (Edelweiss Applied Science and Technology, 2025)
This narrative review explores how Behavior Change Techniques (BCTs) have been applied to promote physical activity, motor skills, and health-related fitness in young adults aged 18–35, and maps their mechanisms onto the COM-B model. Following PRISMA guidelines, studies from 2011–2025 were retrieved from PubMed and Web of Science. After deduplication and screening via EndNote and Zotero, 29 studies were included: 17 experiments, 9 observational studies, 2 reviews, and 1 mixed-methods study. A core triad of goal setting with action planning, self-monitoring with immediate feedback, and social support or comparison appeared in over 60% of studies. This combination increased daily steps or moderate-to-vigorous physical activity within 8–12 weeks and prevented weight gain in interventions lasting 16 weeks or more. Only two studies reported objective motor skill outcomes. Effectiveness was influenced by intervention duration, adherence, gender, and motivational type. Digital tools improved access but required personalization for sustained impact. The multicomponent approach—goal setting, self-monitoring with feedback, and social support—is the most robust pathway to increase activity and maintain weight in young adults. Future research should extend follow-up periods, use objective measures of fitness and skills, and apply adaptive delivery strategies. Trials in cross-cultural settings are also needed to assess real-world scalability and cost-effectiveness.